A review on cosmetics causing conatct urticaria - Merin Shaji; K A Merin; R Kameswaran (Wolters Kluwer Medknow Publications, 2022)
Physical appearance is more strongly pursued than ever in today's world and is considered to provide confidence, success and self-esteem. Cosmetics are the important product in beauty market and their growth is unstoppable. It is estimated that about 95% of women and 75% of men were daily using cosmetics. Despite the considerable use of cosmetics, most people are unaware of its adverse reactions. Urticaria is severe as well as the most common adverse reaction caused by cosmetics. Major cosmetics that cause urticaria include fragrance, preservatives, hair care products, lip plumbers, plant- and animal-derived products, bindi or kumkum, nail cosmetics, glycol peel, permanent makeup and tattoos, etc. This review provides a brief explanation of the cosmetic components that cause urticaria.